2022
DOI: 10.3390/s22155655
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments in Shoulder and Back Kinematics during Repetitive Palletizing Tasks

Abstract: Repetitive task performance is a leading cause of musculoskeletal injuries among order-picking workers in warehouses. The repetition of lifting tasks increases the risk of back and shoulder injuries among these workers. While lifting in this industry is composed of loaded and unloaded picking and placing, the existing literature does not address the separate analysis of the biomechanics of the back and shoulder for these events. To that end, we investigated the kinematics of the back and shoulder movements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The physiological effects of fatigue during repetitive movements, overhead tasks and posture maintenance have been investigated in order to find indicators that can be used to identify fatigue during working activities. Joint angles and torques, especially at shoulder level, significantly reduce with fatigue [ 29 , 30 ]. Moreover, fatigue influences joint coordination that has to compensate for kinematic changes to maintain the trajectory of the end effector [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological effects of fatigue during repetitive movements, overhead tasks and posture maintenance have been investigated in order to find indicators that can be used to identify fatigue during working activities. Joint angles and torques, especially at shoulder level, significantly reduce with fatigue [ 29 , 30 ]. Moreover, fatigue influences joint coordination that has to compensate for kinematic changes to maintain the trajectory of the end effector [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies, instead, directly measure when FSE are found. Most of the studies reported that fatigue is found in industrial tasks in working places [ 150 , 167 ] but also in simulated environments [ 29 , 32 ]. In a limited number of studies, the effects of FSE were not observed or they were under the limit for high risk of MSD development [ 117 , 136 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… When the intelligent forklift inserts the pallet, there are problems of high implementation cost [ 5 ], low algorithm robustness and insufficient accuracy for the calculation of the relative position between the pallet and the forklift. When controlling the intelligent forklift to insert the pallet after the accurate position is calculated, a fixed control amount is usually used without considering the vehicle running state, which makes the control process deviate and eventually leads to errors in the inserting results [ 6 ]. …”
Section: Introductionmentioning
confidence: 99%
“…When controlling the intelligent forklift to insert the pallet after the accurate position is calculated, a fixed control amount is usually used without considering the vehicle running state, which makes the control process deviate and eventually leads to errors in the inserting results [ 6 ].…”
Section: Introductionmentioning
confidence: 99%